Peran Dukungan Organisasional Memediasi Pengaruh Toxic Workplace Environment Terhadap Kesejahteraan Karyawan Travel Agent U2B - Agus Yudi Indrawan Seraya; Ni Wayan Mujiati (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study aims to examine the impact of a toxic workplace environment on employee well-being, mediated by organizational support at U2B Company. The research variables consist of employee well-being as the dependent variable, the toxic workplace environment as the independent variable, and organizational support as the mediating variable. The research method employed is a quantitative associative approach with a sample of 92 employees from U2B Company. The research results are expected to provide theoretical contributions to human resource management and offer practical recommendations for U2B Company to enhance employee well-being through organizational support and improvements in the workplace environment. The limitations of the study include the limited population and the number of variables used. This research is expected to serve as a foundation for future studies to expand the scope of the variables investigated..